Ácaros (Acari) de dois sistemas de cultivo da seringueira no noroeste do Estado de São Paulo - Bellini, Marcos R. [UNESP]; de Moraes, Gilberto J.; Feres, Reinaldo J.F. [UNESP] (My University, 2005)
The cultivation of rubber trees (Hevea brasiliensis Muell. Agr.) has increased considerably in northwestern State of São Paulo. The objective of this work was to evaluate the mite fauna in two cultivation systems commonly found in this region, one in monocrop and other in which it is intercropped with gariroba, Syagrus oleracea (Mart.) Becc. The study was conducted between May 2002 and April 2003, taking monthly samples of 150 leaflets of rubber tree of each plantation and 150 leaflets of gariroba. The faunas of the two systems were similar; the numbers of species, genera and families, as well as the most diverse and abundant families were also similar. Eighteen species were found exclusively on gariroba. The number of mites on the latter was considerably smaller but species richness was larger than on rubber tree. Of the most frequent and abundant mites on rubbe tree, Eutetranychus banksi (McGregor) and Pronematus sp. were the only ones also frequent on gariroba, but much less abundant. None of the predators abundant on rubber tree (Zetzellia aff. yusti, Euseius citrifolius Denmark & Muma, Pronematus sp. e Spinibdella sp.) were significantly abundant on gariroba. The fungus Hirsutella thompsonii Fisher was the only mite pathogen found in this study, attacking Calacarus heveae Feres. Apparently, in the way it is cultivated in the region, gariroba does not represent an adequate reservoir of the most important predatory mites on rubber tree.
Mites (Acari) of two cultivation systems adopted in northwestern State São Paulo
Keywords: Alternative substrate; Biological control; Euphorbiaceae; Pest management; Syagrus oleracea